A Rare Case of Bilateral Orbital Castleman Disease. (August 2014) - Mukherjee, Bipasha; Alam, Mohammad Shahid; Krishnakumar, S.
Abstract Castleman disease is a non-neoplastic cause of lymphadenopathy, first described in 1956 by Dr. Benjamin Castleman. Orbital involvement in Castleman disease is extremely rare. We report a case of bilateral orbital Castleman disease in a 48-year-old Asian male who presented with bilateral inferior dystopia. MRI revealed bilateral extraconal superior orbital mass. Histopathology and immunohistochemistry of the mass revealed features of Castleman disease of hyaline vascular type. Castleman disease should be a differential in suspected idiopathic orbital inflammatory disease and lymphoproliferative disorders.